Infrastructure procurement capacity gaps in Nigeria public sector institutions. Issue 9 (21st October 2019) - Manu, Patrick; Mahamadu, Abdul-Majeed; Booth, Colin; Olomolaiye, Paul Olaniyi; Coker, Akinwale; Ibrahim, Ahmed; Lamond, Jessica
Abstract : Purpose: The achievement of sustainable development goals is linked to the procurement of public infrastructure in a manner that meets key procurement objectives, such as sustainability, value-for-money, transparency and accountability. At the heart of achieving these procurement objectives and others is the capacity of public procurement institutions. Whereas previous reports have hinted that there are deficiencies in procurement capacity in Nigeria, insights regarding critical aspects of organisational capacity deficiencies among different tiers of government agencies is limited. The purpose of this paper is to investigate the critical gaps in the procurement capacity of state and local government agencies involved in the procurement of public infrastructure in Nigeria. Design/methodology/approach: The study employed a survey of public infrastructure procurement personnel which yielded 288 responses. Findings: Among 23 operationalised items that are related to organisational procurement capacity, none is perceived to be adequate by the procurement personnel. Additionally, among 14 procurement objectives only 1 is perceived as being attained to at least a high extent. Originality/value: The findings underscore the acuteness of organisational procurement capacity weaknesses among public procurement institutions within Nigeria's governance structure. It is, thus, imperative for policy makers within state and local government to formulate, resource and implement procurement capacity building initiatives/programmes to address these deficiencies. Additionally, the organisational procurement capacity items operationalised in this study could serve as a useful blueprint for studying capacity deficiencies among public infrastructure procurement agencies in other developing countries, especially within sub-Saharan Africa where several countries have been implementing public procurement reforms.